PROBLEMS AND WAYS TO IMPROVE THE ORGANIZATION OF CARDIOLOGICAL CARE TO THE RURAL POPULATION, IN THE CARDIOLOGISTS OPINION - Anatoliy Ivanyuk; Alexander Kanyura (Bogomolets National Medical University, 2020)
The aim: to study the state, problems and ways of improving the organization of cardialogical care for the rural population in Ukraine based on the materials of a sociological survey of cardiologists. Material and methods The sociological research was carried out according to a specially developed program and covered 352 cardiologists from all regions of Ukraine. Results The main directions for improving the organization of cardialogical care, according to cardiologists opinion, are to increase funding for health care institutions (91,5±1,5%), increase wages (87,2±1,8%), introduce social medical insurance (81,8±2,1%) and mechanisms for economic motivation of personnel (89,8±1,6%); equipping health care institutions with modern medical and diagnostic equipment (73,9±2,3%); improving the quality of postgraduate training of cardiologists (78,2±1,9%); introduction of a health care qua-lity monitoring system (66,9±4,9%); an increase in the economic and legal independence of health care institutions (78,1±2,2); introduction of public-private partnership mechanisms with preservation of health care institutions in state ownership (79,3±2,2%). Conclusions The sociological study found that the main parameters of the organization of cardialogical care for the rural population of Ukraine do not correspond to the economic realities of the time and require modernization.